Viability of thermal imaging in detecting nests of the invasive hornet Vespa velutina. (29th June 2020) - Lioy, Simone; Bianchi, Ettore; Biglia, Alessandro; Bessone, Mattia; Laurino, Daniela; Porporato, Marco
Abstract: Vespa velutina is an invasive hornet species that is colonising Europe, generating considerable impacts on honeybees, beekeeping and biodiversity. Control and early warning strategies for this species are mainly based on monitoring plans and procedures of nest detection and destruction. Technological tools (harmonic radar, radio‐telemetry) have been developed to increase the probabilities of nest detection in new outbreaks. Since hornets are able to regulate nest temperature, thermography may represent an additional technique that may be used, both alone or in support to other techniques. In this study, the viability of thermal imaging in detecting nests of V. velutina was evaluated in controlled conditions. The influence of different environmental and operative variables (time of the day, presence/absence of leaves covering the nest, distance between the nest and the operator) were tested on three nests detected during August 2018 in Italy. All the nests were detectable by thermal imaging, but environmental and operative variables affect their detectability. The temperature difference between the nests and the surrounding reaches its maximum before sunrise and without a tree canopy covering the nests. Although nests were visible in some cases from 30 m, the detectability was higher at shorter distances, even if this variable may also depend on infrared camera resolution. An increase in the environmental temperature also generates a decrease of nest detectability. Although some limitations could occur, these results show the applicability of thermography in detecting V. velutina nests before the beginning of the reproductive phase, and consequently its potentiality in control strategies.